Colonization With Staphylococcus aureus in Atopic Dermatitis Patients: Attempts to Reveal the Unknown - Ogonowska, Patrycja; Gilaberte, Yolanda; Barańska-Rybak, Wioletta; Nakonieczna, Joanna (Frontiers in Microbiology, 2021)
Atopic dermatitis (AD) patients are massively colonized with Staphylococcus aureus (S. aureus) in lesional and non-lesional skin. A skin infection may become systemic if left untreated. Of interest, the incidence of multi-drug resistant S. aureus (MRSA) in AD patients is higher as compared to healthy population, which makes treatment even more challenging. Information on specific genetic background of S. aureus accompanying and/or causing AD flares would be of great importance in terms of possible treatment option development. In this review we summarized the data on the prevalence of S. aureus in general in AD skin, and the prevalence of specific clones that might be associated with flares of eczema. We put our special interest in the presence and role of staphylococcal enterotoxins as important virulence factors in the epidemiology of AD-derived S. aureus. In addition, we present the treatment modality which can be potentially useful as an option of anti-staphylococcal and anti-virulent treatment, namely photochemotherapy based on non-toxic small molecule light-activated compounds, e.g. rose bengal or new methylene blue, which act after visible light activation, and are effective against a wide range of S. aureus including MRSA.